(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Penile cancer is a type of male genital cancer that has a significant impact on patients’ lives and mortality. The inguinal lymph nodes are the primary site of metastasis for penile cancer. Inguinal lymph node dissection directly affects patient prognosis and quality of life. Content: To evaluate the clinical and paraclinical status of lymph nodes, diagnose TNM stages of penile cancer. Surgery is the main method of treating inguinal lymph nodes. Evaluate the results of open inguinal lymph node dissection and laparoscopic inguinal lymph node dissection. Conclusion: Penile cancer can be cured if diagnosed early. Surgery is the main method of radical treatment by treating the primary tumor and lymph nodes, especially bilateral inguinal lymph nodes. Video endoscopic inguinal lymphadenectomy is a technique that can replace open inguinal lymph node dissection in the treatment of penile cancer.